The longitudinal impact of emotional intelligence and psychological empowerment on work engagement among university administrators: a cross-lagged panel model approach - Zhou, Lanfeng; Wang, Xinyu (Frontiers in Psychology, 2026)
BackgroundUniversity administrators face numerous work-related challenges that can impact their emotional intelligence, psychological empowerment, and work engagement. While research on these factors is extensive, longitudinal studies investigating their reciprocal relationships remain limited, and even fewer have examined whether these dynamics differ by gender. This study addresses these gaps by exploring how emotional intelligence, psychological empowerment, and work engagement evolve among male and female university administrators in Putian City, China.MethodsA two-wave longitudinal design was used, with data collected at the start (August 2024 – T1) and end (February 2025 – T2) of an academic semester. This resulted in an overlapping sample of 416 participants who completed surveys at both time points. Validated scales were employed to measure emotional intelligence, psychological empowerment, and work engagement. Cross-lagged panel model (CLPM) and multiple-group analysis were performed to assess the variables’ longitudinal relationships and test for gender differences.ResultsThe findings revealed significant cross-lagged effects: emotional intelligence and psychological empowerment at T1 positively predicted work engagement at T2. Psychological empowerment showed the strongest contribution to later work engagement. Multi-group analyses indicated that these longitudinal associations were highly similar for male and female administrators, with no statistically significant gender differences in path strengths.ConclusionThe findings highlight the dynamic interplay between emotional intelligence, psychological empowerment, and work engagement over time, with both emotional intelligence and psychological empowerment contributing to increased engagement among university administrators. The longitudinal associations were broadly similar for male and female administrators, suggesting that interventions aimed at strengthening emotional and psychological resources may benefit the administrative workforce as a whole.